Assessment of antidiabetic effect of 4-HIL in type 2 diabetic and healthy Sprague Dawley rats. (6th January 2022) - Singh, Pragati; Ishteyaque, Sharmeen; Prajapati, Ramanand; Yadav, Karan Singh; Singh, Rupali; Kumar, Akhilesh; Sharma, Sharad; Narender, Tadigoppula; Mugale, Madhav Nilakanth
Type 2 diabetes mellitus (T2DM) is a metabolic disorder characterized by chronic hyperglycemia and insulin resistance. 4-hydroxyisoleucine (4-HIL) is a non-proteinogenic amino acid isolated from the fenugreek seeds and has enormous pharmacological activities. The present study was undertaken to investigate the antihyperglycemic effect of 4-HIL in streptozotocin (STZ)-induced diabetic rats. Moreover, its toxicity was evaluated in vitro and in vivo employing human embryonic kidney cells (HEK-293) and healthy rats, respectively. In experiment 1, STZ-induced diabetic male rats were subjected to an oral treatment of 4-HIL (100 mg/kg), while experiment 2 deals with the effects of 4-HIL on healthy male and female rats following oral administration. The treatment (experiment 1) declined the elevated blood glucose level, feed intake, and increased body weight(s). Additionally, blood glucose impairment was improved as observed by OGTT and IPGT tests. Pancreatic histopathology revealed mild changes in the 4-HIL group. Moreover, experiment 2 showed increased body weight, normal blood glucose levels (male—106.06 ± 7.49 mg/dl and female—100.06 ± 14.69 mg/dL), hematological parameters, and histopathological profiles in the treatment group. 4-HIL did not affect the viability of HEK-293 cells, and no signs of toxicity were observed in healthy rats. Therefore, the study concludes that 4-HIL has potential antihyperglycemic activity without any toxic effects.